THE DETERMINANTS OF KSA MILLENNIAL BEHAVIOR TOWARD ORGANIC AND SUSTAINABLE PRODUCTS - Marwah Alqashqari; Hanen Charni (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The current study investigates how consumers in KSA think of organic and sustainable products, as the demand of consumers toward organic food and product has expanded through the nations in the recent years. This study will target the millennials consumers who has the concern of organic and sustainability in which the survey has examined the behavior of consumers and their intention to buy an organic product in the KSA markets. This study used quantitative approach and online survey questionnaire to gather the primary data in order to test the proposed hypotheses. The findings indicate that there is a strong relationship between health consciousness and purchase intention. The result of this study shows that the majority of people were aware about the concept of organic product but limited by the superiority of charged price, lack of availability of this kind of product in the KSA market. Hence, this study will hopefully help marketers to estimate the opportunity of KSA markets in developing the tools to achieve advantages through competitive market.